The World of Translation - Harliani, Susi (OKARA: Jurnal Bahasa dan Sastra, 2019)
Basically, transferring message from the source to target language is not just changing the language, as there is multidiscipline process in the translation. The complexity performed since the language is multi-system and its variety in communication is never apart from context. Therefore, the translation needs not only linguistics theory but also some other theories like socio-linguistics, psycholinguistics, pragmatics, contrastive analysis and cross culture understanding.